Ovarian Sertoli-Leydig cell tumour with α-fetoprotein-producing intestinal glandular cells. Clinical case and short review of basic literature - Strus, Michał; Rajtar-Ciosek, Agnieszka; Jach, Robert; Hankus, Jerzy; Szczepański, Wojciech (Polish Journal of Pathology, 2019)
Sertoli Leydig cell tumor of the ovary, is a rare neoplasm from the group of sex cord-stromal tumors of the ovary, accounting for less than 1% of all ovarian tumors. Among the Sertoli Leydig cell tumors, we distinguish a separate group of tumors secreting α-fetoprotein (AFP). The young 24-year-old woman presented to the Clinical Department of Gynaecological Endocrinology at the University Hospital in Krakow due to secondary amenorrhea, hirsutism and worsening abdominal pain for several months. During the admission draws attention was drawn to the abnormal level of testosterone, AFP and the revised structure of the ovary in the ultrasound. After a preliminary diagnosis, expanded pelvic MRI was performed, which found an isolated tumor derived from Sertoli Leydig cells. The patient was enrolled to unilaterally remove the right ovary by laparotomy. Histopathological examination and immunohistochemical staining confirmed the diagnosis of Sertoli Leydig cells tumor, and in pathological examination we found glandular mucosa cells of the colon. Owing to scientific reports on the stromal tumors of the ovary, we decided to perform genetic testing and verify the patient’s karyotype. In the follow-up 90 days after the surgery, levels of testosterone and AFP were correct. In case of Sertoli Leydig cell tumors, especially in young women of childbearing potential, special attention should be paid to Anti-Mullerian hormone testing before surgery, as well as genetic diagnostics to exclude disorders of sex development.